NORMALIZATION OF COMMUNITY LIFE AFTER CONFLICT: Reconciliation Measures Return To The Village - Rohman, Abid; Rosidi, Achmad; Setiyani, Wiwik (TASAMUH, 2022)
Returning together with family and community is a dream for people who experience conflict caused by various socio-religious problems. The rolling cases between adherents of Sunni-Shi’i religious ideologies have found common ground after the conflict. Various efforts to create a peaceful and fairness require the roles of religious leaders, community leaders, and the government. The academic problem that will be explained is to unite views on conflicting groups in realizing the harmonious life of the Sampang community. The method used is depth interviews with people involved in the conflict, especially in Karang Gayam and Blu'uran villages. Data analysis was carried out using the theory of reconciliation to realize the normalization of people's lives as a form of social acceptance. The Sampang community wish for a peaceful life, mutual respect, and appreciation in social life. Normalization efforts can be carried out with a reconciliation approach, namely; top-down and bottom-up. The Sampang community is open to accepting the agreed agreement. Thus, normal life can be realized. Conflict is a necessity. However, reconciliation is a must to create a normal life such as peace, mutual respect, and respect for one another